2016
DOI: 10.17749/2313-7347.2016.10.2.016-022
|View full text |Cite
|
Sign up to set email alerts
|

Hemostasis in Patients With Hematoma Retrochorial

Abstract: Данная интернет-версия статьи была скачана с сайта http://www.gynecology.su Не предназначено для использования в коммерческих целях.Информацию о репринтах можно получить в редакции. Тел.:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Indicators of the hemostasis system in patients with normal pregnancy and those with retrochorial hematoma are presented in Table 2 . The values of PT, aPTT, TT, fibrinogen, SFMC, D-dimer, and activity and concentration of PG for healthy pregnant women were within the normal range ( Table 1 ) [ 21 , 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indicators of the hemostasis system in patients with normal pregnancy and those with retrochorial hematoma are presented in Table 2 . The values of PT, aPTT, TT, fibrinogen, SFMC, D-dimer, and activity and concentration of PG for healthy pregnant women were within the normal range ( Table 1 ) [ 21 , 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Often, the concentration of fibrinogen degradation products in the mother’s blood does not reflect the state of the fibrinolytic system and its main component, plasminogen. In a study on the assessment of hemostatic parameters in pregnant women with retrochorial hematoma, the authors showed that elevated levels of D-dimer and hypercoagulability may indicate the formation of retrochorial hematoma [ 22 ].…”
Section: Introductionmentioning
confidence: 99%